(untitled) (Scientia Agropecuaria, 2024)
Corn ear rot caused by species of the Fusarium genus is one of the many problems faced by producers worldwide due to its wide geographical distribution, leading to various diseases such as stalk, root, and ear rot. The identification of the pathogen can be carried out through morphological and molecular techniques, with the latter being necessary for species-level identification. Additionally, the pathogen can produce mycotoxins such as Deoxynivalenol (DON), Zearalenone (ZEA), and Fumonisins (FB), which contaminate the grain, posing a risk to both human and animal health. It has been reported that the pathogen can survive in crop residues, entering the plant through the roots, often via wounds caused by insects or agricultural practices. Once inside the roots, the phytopathogen colonizes the xylem vessels and is transported through the plant’s vascular system, spreading systemically within the plant, colonizing the stalk and other vascular tissues, and eventually reaching the ear. The introduction of resistant cultivars, crop residue management, irrigation, and biological control of diseases are key strategies in agricultural practices to reduce the incidence and spread of diseases caused by Fusarium. However, current and future challenges include the increasing resistance of strains, distribution, and methods for pathogen identification.